PHENOTYPIC PERFORMANCE OF CIHERANG SUB1 NEAR ISOGENIC LINE AS AN ADAPTIVE VARIETY FOR FLOODING CONDITIONS - Yudhistira Nugraha; Nurul Hidayatun; Trisnaningsih Trisnaningsih; Dini Yuliani (Indonesian Journal of Agricultural Science, 2017)
Marker assisted back crossing (MABC) is a molecular tool that can help breeders in reducing backcrossed generation. However, effectiveness of this method still needs further approval using actual phenotypic performances. The International Rice Research Institute had developed Ciherang near isogenic line (NIL) of submergence tolerance, Sub1. The study aimed  to evaluate phenotypic performances of Ciherang Sub1 NIL in the greenhouse and field conditions. The study was conducted  in ten locations using five submergence-tolerant varieties and a control treatment under normal conditions. The results showed that the average grain yields and some agronomic traits of Ciherang Sub1 were not significantly different compared with those of Ciherang (recurrent parent). However, under 10- and 15-days of submergence. Ciherang Sub1 was significantly different to Ciherang. The survival rate of Ciherang Sub1 was higher than Ciherang after 14-days submerged in the greenhouse tank experiment. Response of Ciherang Sub1 to brown planthopper biotype 1, 2 and 3, Xanthomonas oryzae pathotype III, IV and VIII, and rice tungro virus inocula from Subang, Magelang and Lanrang were also comparable with its recurrent parent. Quality and physico-chemical properties of rice (milled rice) of Ciherang Sub1 were not different with those of Ciherang. Similarity level of phenotypic traits of Ciherang Sub1 compared to Ciherang was more than 87.5%. This finding proved that a single backcross method can produce progeny identic with its parent. This MABC line can be recommended to farmers in flood-prone area where the Ciherang is preferred.